Diskursus Konsep Jemaat Vital terhadap Minimnya Partisipasi Pemuda dalam Pelayanan Gereja - Nova Clara Kakisina; Martha Marselina Patty (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2023)
This article aims to describe and analyze the problems of youth in the GPM Liliboy Congregation who are not active in church services, specifically as liturgical participants at Sunday services. This congregation has a total of 566 members who fall into the youth age category of 17-45 years. This age category is based on the age of the Maluku Protestant Church Youth Generation. The research method used is qualitative research, namely through interviews but also using other sources by involving congregation development perspective. This study aims to determine the theological views of youth about service and the factors that cause youth to be inactive as liturgical supporters in Sunday services. The results of this study found that youth were not active in church services due to two factors, namely internal factors and external factors. The youth's inactivity in church ministry is a complex problem that the church and the youth themselves have to deal with jointly. Youth is the baton of the church that will continue the mission of the church's ministry in the future. Congregation development does not only emphasize ritual aspects; it is also a practical effort that can empower existing human potential, including church youth.